Quantitative modelling of amino acid transport and homeostasis in mammalian cells - Gregory Gauthier-Coles (Nature Portfolio, 2021)
Cytosolic amino acid concentrations are carefully maintained, but how homeostasis occurs is unclear. Here, the authors show that amino acid transporters primarily determine intracellular amino acid levels and develop a model that predicts a perturbation response similar to experimental data.